7 - Deploying the Electronic Edge in the Peer Review of Scholarly Publications - Nwagwu, E. Williams (Africa Media Review, 2007)
This paper traces the origin and evolution of the traditional peer review system, and shows its strengths and weaknesses, which arise mainly due to the effects of human factors in the management of activities involved. An automated nonblinded open peer review system is recommended considering the versatility of the information and communication technologies and the modern openness culture in scholarly communication. This new system will improve the participation of developing countries’ scholars in the review of scientific papers published in the mainstream journals, and thereby enhance their contribution in the international science scene.